The Pedagogy of the Open Society - Peters, Michael A. author. aut Link
XIV, 128 p.
Keywords: Social processes and policies that foster openness as an overriding value as evidenced in the growth of open source, open access and open education and their convergences that characterize global knowledge communities that transcend borders of the nation-state. Openness seems also to suggest political transparency and the norms of open inquiry, indeed, even democracy itself as both the basis of the logic of inquiry and the dissemination of its results. Openness is a value and philosophy that also offers us a means for transforming our institutions and our practices. This book examines the interface between learning, pedagogy and economy in terms of the potential of open institutions to transform and revitalize education in the name of the public good.